Diesel exhaust particle promotes tumor lung metastasis via the induction of BLT1-mediated neutrophilic lung inflammation. (November 2018) - Li, Wenjing; Liu, Ting; Xiong, Yingluo; Lv, Jiaoyan; Cui, Xinyi; He, Rui
Highlights: DEP exposure induced LTB4 production and neutrophils infiltration and promoted lung metastasis of 3LL or 4T1 tumor cells. BLT1 blockade attenuated DEP-induced neutrophilic lung inflammation. BLT1 blockade before inflammation onset, but not after tumor cell seeding inhibited DEP-enhanced lung metastasis. BLT2 blockade failed to inhibit DEP-induced lung inflammation and tumor metastasis. Abstract: BLT1, the primary functional receptor of Leukotriene B4 (LTB4), is involved in tissue inflammation by mediating leukocyte recruitment, and recently LTB4-dependent inflammation was reported to promote lung tumor growth. Exposure to diesel exhaust particle (DEP), the major component of particulate matter 2.5 (PM2.5 ), can elicit lung inflammation, which may increase the risk of lung cancer. However, it remains unknown about the critical factors mediating DEP-induced lung inflammation and the subsequent effect on tumor metastasis. In this study, we found that DEP exposure led to acute lung inflammation, characterized by abundant infiltration of neutrophils and elevated lung levels in LTB4, as well as several pro-inflammatory cytokines and chemokines, including IL-1β, IL-6, TNF-α, CXCL1/2. Furthermore, DEP exposure promoted lung metastasis of 3LL and 4T1 cells. BLT1 blockade by its specific antagonist U75302 significantly inhibited neutrophilic lung inflammation following DEP exposure. Importantly, BLT1 blockade before the onset of inflammation significantly reduced DEP-enhanced lung metastasis, which was associated with greatly decreased infiltrating neutrophils in lungs. Interestingly, BLT1 blockade after the occurrence of lung metastases had no effect on the magnitude of lung metastasis, suggesting that inhibition of BLT1-mediated lung inflammation was insufficient to suppress established metastatic tumor. Administration of BLT2 inhibitor LY255283 fails to inhibit DEP-induced lung inflammation and tumor metastasis. Collectively, our results demonstrate that DEP exposure causes BLT1-mediated lung neutrophilic inflammation, which is critical for tumor lung metastasis, and suggest that interruption of the LTB4-BLT1 axis could be useful for preventing PM2.5 -induced inflammation and subsequent susceptible to lung metastasis.